Development of Digital Payment Systems in Indonesia - Hendrawan, Muhammad Ridho Nur Alamsyah; Marits, Shofi Arofatul; Herman, Sebastian (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research explores the dynamics and development of the digital payment system in Indonesia along with rapid technological transformation, including the growth of the digital finance industry and a shift in consumer behavior towards non-cash transactions. The aim of this research is to analyze the impact of the development of digital payment systems on the existence of cash in the digital economy era as well as reduce risks that may arise from the use of digital payment systems and prevent price increases due to the amount of cash in circulation. The method used in this research is a qualitative method with a phenomenological approach. Data was analyzed involving measuring and testing data by considering theoretical concepts related to the development of digital payment systems. The results of this research indicate that technological progress in the digital economy era, especially in the development of digital payment systems, has increased rapidly. The COVID-19 pandemic has accelerated the use of e-commerce and digital wallets, triggering digital transformation in the Micro, Small and Medium Enterprises (MSME) sector. Efforts from governments, regulators and service providers to maintain user security and privacy are important steps to build public trust in digital payments.